Evaluation of Mortality Magnitude among Holstein Friesian Calves and its Risk Factors Evaluation in an Organized Farm of Quetta Pakistan - Achakzai, Kamran Baseer; Shah, Muhammad Abbas; Achakzai, Ramla; Kakar, Ghulam Hussain; Harifal, Muhammad Anwar (Nepalese Journal of Agricultural Sciences, 2025)
A 24-year (1999-2022) retrospective study investigated calf mortality and its causes in Holstein Friesian calves. Divided into eight periods, the data explored how time, season, sire, sex, age and cause of death impacted mortality. Female calves exhibited significant variation (P<0.01) across these periods. The highest mortality (28%) for females occurred during period 4 (2008-2010), while the lowest overall mortality (5% for both sexes) was observed in period 6 (2014- 2016). Season also significantly affected (P<0.01) mortality in both sexes and overall. Spring had the highest rates (16% overall, 13% male, 21% female), while summer comprehended the lowest (4% overall, 2% male, 8% female). Interestingly, sire selection played a crucial role on mortality, calves from natural sires had the highest mortality (25%), whereas calves born via artificial insemination with imported semen from different bulls exhibited varying mortality rates. No clear pattern emerged in the overall mortality across different age groups. Finally, a significant relationship (P<0.01) was observed between calf mortality and occurrence of various diseases. Gastrointestinal diseases were the leading cause of death (44%), followed by a group of other diseases (25%) including lower mortality causes like respiratory (13%), Foot and Mouth Disease (10%) and the lowest mortality observed was attributable to tick-borne illnesses (8%). These findings highlight potential risk factors like season, sire selection and disease prevention strategies to reduce calf mortality and morbidity in Holstein Friesian herds.